Analysis of Prerequisites for the Creation of a Second-Generation Dual-Mode Traction-Levitation Module - Mukha, A. M.; Plaksin, S. V.; Ustymenko, D. V.; Shkil, Yu. V.; Kitayev, O. V.; Antoniuk, A. P. (Science and Transport Progress, 2025)
Purpose. This work aims to develop a concept for a dual-mode traction-levitation module as a basic element of an effective system for synchronized control of the motion and suspension of a maglev train and to analyse the prerequisites for its creation. Methodology. The features of the functioning and control of the main subsystems of the existing maglev transport, their engineering solutions in terms of linear traction electric drive and magnetic suspension were studied. Theories and methods of electric traction, electric machines, electrical engineering, and electronics were used to modify the structure and parameters of the traction linear drive, the magnetic suspension system, and the methods of controlling the traction-levitation system of the maglev. Finding. The current implementation of magnetic levitation transport systems represents a step-by-step modernization of classic approaches that were available at the end of the last century. At the same time, progress in renewable energy, microelectronics, low-temperature technology, and radio navigation has laid the foundation for the development of the next generation of magnetic levitation transport, based on a basic dual-mode traction-levitation module powered by photovoltaic converters. It is shown that improvements in maglev technology can be achieved through the essential integration and coordinated combination of two methods of creating magnetic levitation—electromagnetic (EMS) and electrodynamic (EDS)—thanks to the use of a fundamentally different architecture for the construction of the Maglev track—not from long sections with three-phase power coils, but with discrete modules capable of performing the tasks of creating propulsive force (traction mode) and magnetic suspension, across the entire range of available speeds. An analysis of currently available technologies gives confidence that the creation of a dual-mode traction-levitation module, as well as a corresponding train motion control system, is a completely solvable problem. Originality. The results obtained provide a scientific basis for the development and improvement of the process of creating an effective and competitive next-generation magnetically levitated ground transportation system. Practical value. Building a Maglev transport system using standard dual-mode hybrid traction-levitation modules will, first, significantly improve the energy performance of this type of transport by locally placing photovoltaic converters and modules, which will reduce energy transmission losses, as well as the use of renewable energy sources (photoelectric distributed energy system), secondly, simplify the design of the track structure by integrating the functions of levitation and traction in a single node, and thirdly, reduce capital and operating costs through the use of a unified base module.